PRA PERANCANGAN WATERBUS DENGAN PENGGERAK MOTOR LISTRIK BERTENAGA SURYA DI BANJIR KANAL BARAT JAKARTA - Budiarto, Untung (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2010)
The problems of traffic jams and the issues of energy problems in Jakarta have been generated an innovation and an alternative solution in public transportation development which can reducing these problems that using the renewable energy Referring to the condition and these problems, the concept must be done within pre-design of waterbus which equipped with a solar panel system engine. The using of solar system as an energy resource on the pre design of the ship must be suitable on the water condition, the selection of the solar panel, 3 dimensional with sail routes and analysis calculation when the ship sailing The research is aimed to produce main dimensional of the ship which LOA = 12,00 m, LWL = 11,47 m, Bm = 4,34 m. This ship is using two outboard electrical motors which producing 2 KW of power, 15,954 watt of battery and 52,12 m2 of solar panel with monocrystaline type with 5,520 watt of power which defined from speed of the ship at 5,25 knot with 0,4 KN resistance